Identification of QTLs for Drought-Related Traits in Alien Introgression Lines Derived from Crosses of Rice (Oryza sativa cv. IR64) × O. glaberrima under Lowland Moisture Stress - Bimpong, I.K.; Serraj, R.; Chin, J.H.; Ramos, J.; Mendoza, E.T.M.; Hernandez, J.E.; Mendioro, M.S.; Brar, D.S. (Springer, 2011)
Drought is a major abiotic stress that limits rice productivity in rain-fed and upland ecosystems. African rice, Oryza glaberrima, has low yields but is tolerant to drought and other stresses. We evaluated 513 BC2F3 progenies from alien introgression lines (AILs) that were derived from crosses of Oryza sativa (IR64) × O. glaberrima. They were assessed for yield and other traits when grown under drought at two locations. Such conditions reduced grain production by 59% compared with the recurrent parent (IR64). However, 33 AILs had higher yields, thus demonstrating their potential as genetic material for transferring drought-related traits from O. glaberrima to O. sativa. A set of 200 AILs was selectively genotyped with 173 simple sequence repeat and sequenced tagged site markers. Molecular analysis showed that a mean of 4.5% of the O. glaberrima genome was introgressed in BC2F3 AILs. Our analysis revealed 33 quantitative trait loci (QTLs; including 10 novel) for different traits. O. glaberrima contributed 50% of the alleles to those newly identified QTLs, with one for grain yield per plant (ypp9.1) being new. A QTL at RM208 on chromosome 2 positively affected yield under stress, accounting for 22% of the genetic variation. Our identification of drought-related QTLs for yield and yield components will be useful to future research efforts in marker-assisted selection